The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1021/ja711278c
|View full text |Cite
|
Sign up to set email alerts
|

Imprinting of Molecular Recognition Sites through Electropolymerization of Functionalized Au Nanoparticles: Development of an Electrochemical TNT Sensor Based on π-Donor−Acceptor Interactions

Abstract: Electrochemical sensors for the analysis of TNT with enhanced sensitivities are described. The enhanced sensitivities are achieved by tailoring pi-donor-acceptor interactions between TNT and pi-donor-modified electrodes or pi-donor-cross-linked Au nanoparticles linked to the electrode. In one configuration a p-aminothiophenolate monolayer-modified electrode leads to the analysis of TNT with a sensitivity corresponding to 17 ppb (74 nM). In the second configuration, the cross-linking of Au NPs by oligothioanili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
183
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(185 citation statements)
references
References 71 publications
2
183
0
Order By: Relevance
“…This necessitates a need to develop a novel and modernistic method to fabricate a solid template-based sensor on a large scale for technological applications. A very few methods effectively demonstrated the sensing permanence of TNT in real time application [16,[26][27][28][29][30][31][32][33][34][35][36]. For example Daming Gao reported a resonance energy transfer-amplifying fluorescence quenching at the surface of silica nanoparticles for the ultrasensitive detection of TNT in solution and vapor environments [17].…”
Section: Smart Hybrid Sensormentioning
confidence: 99%
“…This necessitates a need to develop a novel and modernistic method to fabricate a solid template-based sensor on a large scale for technological applications. A very few methods effectively demonstrated the sensing permanence of TNT in real time application [16,[26][27][28][29][30][31][32][33][34][35][36]. For example Daming Gao reported a resonance energy transfer-amplifying fluorescence quenching at the surface of silica nanoparticles for the ultrasensitive detection of TNT in solution and vapor environments [17].…”
Section: Smart Hybrid Sensormentioning
confidence: 99%
“…During the past ten years, the literatures on the development of MIP-based sensors, in particularly electrochemical (Riskin et al, 2008;) and optical (McDonagh et al, 2008;BasabeDesmonts et al, 2007;Li J. et al, 2007a;Feng et al, 2008) sensors, have been dramatically growing (Nilsson et al, 2007;Ramanavicius et al, 2006). It was found that the manufacture of composites consisting of molecularly imprinted conducting polymers results in obtaining materials that exhibit both predetermined selective molecular recognition and electrical conductivity (Deore et al, 2000).…”
Section: Mips In Chemical Sensingmentioning
confidence: 99%
“…Because the template concentration was a key factor when imprinted sites had to be generated, in this work a semiorganic media was chosen to carry out the electrogeneration of the copolymer in order to favor the dissolution of the template molecules. Although the amount of the imprinted sites increases with the increase of the imprinted membrane thickness, thick imprinted membranes could lead to slow diffusion of analytes to the recognition sites and to inefficient communication between the binding sites and transducers (Riskin et al, 2008). To further increase the amount of effective imprinted sites on the sensor surface, the simplest method is to use a higher electrode surface area (He et al, 2008) through the assembly of gold nanoparticles (AuNPs) at the surface of electrodes (Daniel & Astruc, 2004;Feng et al, 2008;Yu et al, 2003) due to its large specific surface area, good biocompatibility and high conductivity.…”
Section: Molecularly Imprinted Polymer Strategy Applied To the Develomentioning
confidence: 99%